Positional differences in decision-making situations during professional rugby league match-play - Turek, L.; Doma, K.; Sinclair, W.; Connor, J. (Journal of Human Kinetics, 2024)
The aim of this study was to explore the types and frequency of decision-making situations of rugby league players during defensive situations and examine whether they were predictive of key performance indicators (KPI). Fifteen elite rugby league matches were coded using notational analysis methods. Specific defensive situations were analysed, including the number of: one-on-one situations with an opposing attacker (1-on-1), two-on-one situations (2-on-1), and combined 1-on-1 and 2-on-1 situations (i.e., total decisions; TDs). There was no relationship between the game outcome and game KPIs for TDs or 1-on-1 decision-making situations. However, successful tackles and missed tackles were predictive of 2-on-1 decision-making situations. Positional differences revealed that back rowers were exposed to the greatest number of decision-making situations, while wingers had the lowest exposure. The total number of decisions and the number of 1-on-1 decisions made by the centres and wingers were significant predictors of line breaks. Additionally, 2-on-1 decisions were significant predictors of line breaks for backrowers. The findings of this study suggest that the type and frequency of decision-making situations in Rugby League are position specific. Practical applications for coaches are discussed to ensure that practice approaches are representative of the various defensive decision-making demands players experience during a game, based on their position.